Problem Based Learning Design Based on Culturally Responsive Teaching for Understanding the Concept of Opportunity - Drajat, Widi Rahmawati; Gunandi, Farid; Rosyadi, Rosyadi; Komariah, Komariah (STKIP Singkawang, 2025)
This study aims to develop a mathematics learning design that integrates Problem-Based Learning (PBL) with the Culturally Responsive Teaching (CRT) approach to improve the understanding of probability among Grade XII SMK students. The background of this study is the problem of low student understanding of probability material caused by minimal mathematical reasoning skills, low motivation to learn, and the dominance of conventional methods such as lectures and practice questions. Students also have difficulty solving contextual problems and applying enumeration rules. The CRT approach is considered to make learning more relevant because it links the material to the student's cultural background, while PBL encourages active participation and the development of critical thinking skills through solving real problems. The research method used is the 4D development model, which consists of the Define, Design, Develop, and Disseminate stages. In the Define stage, a needs analysis is conducted through teacher interviews to determine the challenges and readiness to implement PBL-CRT-based learning. The design stage produces a prototype of the learning design, teaching modules, and evaluation tools. The development phase includes a feasibility test by experts, a practical test in the classroom, and an effectiveness test by analyzing students' interests and learning outcomes. The results of the feasibility test showed that the module was feasible to use (Asymp. Sig = 0.004 <0.05), the practicality test obtained a score of 4 and 5 out of 97%, and the effectiveness test showed that the module significantly increased learning interest (Sig. = 0.01 <0.05). The dissemination phase was carried out by distributing the learning products online through the website. The results of the study showed that the learning design combining PBL and CRT can significantly improve students' understanding of mathematical concepts and create a learning atmosphere.Desain Pembelajaran Problem Based Learning Berbasis Culturally Responsive Teaching terhadap Pemahaman Konsep PeluangABSTRAKPenelitian ini bertujuan untuk mengembangkan desain pembelajaran matematika yang mengintegrasikan Problem Based Learning (PBL) dengan pendekatan Culturally Responsive Teaching (CRT) guna meningkatkan pemahaman konsep peluang pada siswa kelas XII SMK. Latar belakang penelitian ini adalah rendahnya pemahaman siswa terhadap peluang materi, yang disebabkan oleh minimnya keterampilan penalaran matematis, rendahnya motivasi belajar, serta dominasi metode konvensional seperti ceramah dan latihan soal. Siswa juga kesulitan dalam menyelesaikan soal kontekstual dan menerapkan kaidah pencacahan. Pendekatan CRT dinilai mampu menjadikan pembelajaran lebih relevan karena materi terkait dengan latar belakang siswa, sementara PBL mendorong keterlibatan aktif dan pengembangan kemampuan berpikir kritis melalui pemecahan masalah nyata. Metode penelitian yang digunakan adalah model pengembangan 4D, yang terdiri atas tahapan Define, Design, Develop, dan Disseminate. Pada tahap Define, dilakukan analisis kebutuhan melalui wawancara dengan guru untuk mengetahui tantangan dan kesiapan penerapan pembelajaran berbasis PBL-CRT. Tahap Desain menghasilkan prototipe rencana pembelajaran, modul terbuka, dan instrumen evaluasi. Tahap Pengembangan meliputi uji kelayakan oleh para ahli, uji kepraktisan di kelas, serta uji efektivitas melalui analisis minat dan hasil belajar siswa. Hasil uji kelayakan menunjukkan modul layak digunakan (Asymp.Sig = 0.004 < 0.05), uji kepraktisan memperoleh skor 4 dan 5 sebesar 97%, dan uji efektivitas menunjukkan bahwa modul meningkatkan minat belajar secara signifikan (Sig. = 0.01 < 0.05). Tahap Disseminate dilakukan melalui penyebaran produk pembelajaran secara berani melalui website. Hasil penelitian menunjukkan bahwa desain pembelajaran yang menggabungkan PBL dan CRT mampu meningkatkan pemahaman konsep matematika siswa secara signifikan, serta menciptakan suasana belajar yang lebih inklusif, kontekstual, dan relevan dengan pengalaman serta budaya siswaKata Kunci :problem based learning; culturally responsive teaching; peluang; desain pembelajaran; pemahaman konsep